Traditional massage therapy-induced traumatic rupture of hydronephrosis secondary to ureteral obstruction: a case report - Dahril; Jufriady Ismy; Muhammad Puteh Mauny; Yasser Kuddah; Richardo Richard Handoko; Muhammad Azmi Fanany; Bellinda Paterasari; Andreas (Journal of International Surgery and Clinical Medicine, 2021)
Introduction: The vast majority of renal injuries occurred by blunt mechanisms with fall and motor vehicle crashes. Massage therapy is widely used as traditional medicine and has been viewed as a safe treatment tool without major complications or side effects. Renal rupture due to traditional massage therapy is a rare complication. Moreover, it occurs even less commonly considering the anatomical location of the kidneys, where they are well-protected. The purpose of this article is to present a case of a patient with an acute ruptured kidney due to traditional massage therapy four hours before admission to the hospital. Case description: A 52-years-old man came to the emergency department with right upper and lower abdominal pain. The pain began in the flank region and spread to the right lower abdomen. He visited a traditional massage therapist and received massage therapy in the abdominal and back region with no history of other trauma or other activities before admission. The hemodynamic status was unstable. Physical examination revealed tenderness in the right upper and lower abdominal region and bulge area at the right flank region. We performed an emergency laparotomy due to hemodynamic instability. Right retroperitoneal exploration revealed active bleeding from a ruptured right kidney. Thus right nephrectomy was performed. Post-operative non-contrast CT scan showed ureteral obstruction due to the presence of right distal ureteral stone Conclusion: Kidneys with anatomical abnormalities such as hydronephrosis and blunt abdominal trauma may increase pressure in the hydronephrotic renal pelvis and cause a rupture. We suggest that surgeons should be cautious of the possibility of renal rupture in blunt trauma due to the change of normal morphological structure of the kidney and attenuation of the renal parenchyma.